2020
DOI: 10.1002/pro.3843
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analysis of a sugar 4,6‐dehydratase from Acanthamoeba polyphaga Mimivirus

Abstract: The exciting discovery of the giant DNA Mimivirus in 2003 challenged the conventional description of viruses in a radical way, and since then, dozens of additional giant viruses have been identified. It has now been demonstrated that the Mimivirus genome encodes for the two enzymes required for the production of the unusual sugar 4-amino-4,6-dideoxy-D-glucose, namely a 4,6-dehydratase and an aminotransferase. In light of our long-standing interest in the bacterial 4,6-dehydratases and in unusual sugars in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…The electron density for the dinucleotide shows that the NADP + had been hydrolyzed to ADP‐ribose 2′‐phosphate. This phenomenon has been previously observed in several of our structural investigations on dinucleotide‐dependent enzymes, and it is most likely an artifact of the experiment 17,20 . The electron density for the dinucleotide in subunit 2 also indicated that the nicotinamide ring had been hydrolyzed from the cofactor.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…The electron density for the dinucleotide shows that the NADP + had been hydrolyzed to ADP‐ribose 2′‐phosphate. This phenomenon has been previously observed in several of our structural investigations on dinucleotide‐dependent enzymes, and it is most likely an artifact of the experiment 17,20 . The electron density for the dinucleotide in subunit 2 also indicated that the nicotinamide ring had been hydrolyzed from the cofactor.…”
Section: Resultssupporting
confidence: 73%
“…16 We recently reported the X-ray structure of R141 from Mimivirus to 2.05 Å resolution. 17 Our results demonstrated several significant architectural differences between the Mimivirus 4,6-dehydratase and those previously characterized bacterial enzymes. As a continuation of our studies on sugar-modifying enzymes from Mimivirus, herein we report a structural and enzymological characterization of L780.…”
supporting
confidence: 56%
See 3 more Smart Citations